2004
DOI: 10.1002/aic.10079
|View full text |Cite
|
Sign up to set email alerts
|

Sonophotocatalytic reactors for wastewater treatment: A critical review

Abstract: The common optimum operating conditions for sonochemical and photocatalytic oxidation coupled with the similarity in the mechanism

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(80 citation statements)
references
References 180 publications
(234 reference statements)
3
77
0
Order By: Relevance
“…The pollutant and thus the sonophotocatalytic degradation rates will be maximum near the point of zero charge of the catalyst as 6.8. 27,28 This is in agreement with the higher COD Cr removal efficiency observed for the DDVP under sonophotocatalysis at pH 7.3. Considering that dichlorvos is a unionizable compound, the increase of the reaction at alkaline pH can be ascribed to the high hydroxylation of the surface of the catalyst due to the presence of a large quantity of OH − ions.…”
Section: Methodssupporting
confidence: 86%
“…The pollutant and thus the sonophotocatalytic degradation rates will be maximum near the point of zero charge of the catalyst as 6.8. 27,28 This is in agreement with the higher COD Cr removal efficiency observed for the DDVP under sonophotocatalysis at pH 7.3. Considering that dichlorvos is a unionizable compound, the increase of the reaction at alkaline pH can be ascribed to the high hydroxylation of the surface of the catalyst due to the presence of a large quantity of OH − ions.…”
Section: Methodssupporting
confidence: 86%
“…The difficulty of tailoring both frequency and amplitude at a time, together with the directional sensitive effect of ultrasound and its non-uniform volumetric energy density, are the main drawbacks of ultrasound cavitation that may complicate its scale-up [21][22][23][24]. A highintensity, bulk and multi-frequency type of excitation would be the ideal acoustic wave.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that TiO 2 photocatalysis combined with ultrasound can be benefited [72,97,159,160] due to different factors like (a) an increase in the catalyst surface area due to the aggregation action of ultrasound, which enhances the performance of the photocatalytic system [161]; (b) an improvement of mass transfer of organic compounds between the liquid phase and the TiO 2 surface [162,163]; and (c) a reduction of charge recombination and promotion production of additional OH • due to the residual H 2 O 2 generated [162,163]. Also, the continuous cleaning of the TiO 2 surface by acoustic cavitation [164] might also have some role in modifying the photocatalytic rate. Tables 4-6 show that different amounts of catalyst ranging from 10 mg L −1 to 4 g L −1 yielded different degrees of organic degradation during the photocatalytic oxidation process under the experimental conditions stated.…”
Section: Influence Of Catalyst Concentrationmentioning
confidence: 99%
“…It has been reported that the adsorption of the organic compounds onto the TiO 2 surface is affected by the pH of the solution [97,160]. The pollutant and thus the rates of degradation will be maximum near the point of zero charge (pzc) of the catalyst [164]. The pzc of TiO 2 surface is at pH pzc between 6.25 and 7.1 [1,165,166], depending on the ionic strength [166].…”
Section: Influence Of Initial Pollutantmentioning
confidence: 99%